Evaluation of Antibiotics for Inpatients with Acute Respiratory Tract Infections at Tamiang Layang Regional General Hospital in 2023 - Nadya Ayu Nida; Hasniah; Ramadhani, Juwita (Brawijaya University, 2026)
The high rate of acute respiratory infections (ARI) is a crucial health issue, the therapy usually used is antibiotics, but there is still inappropriate use, therefore an analysis is needed to ensure an antibiotic has been used rationally or not. This study aims to identify profiles and evaluate antibiotic use using the ATC/DDD, DU90% and Gyssens methods. Data were collected retrospectively from medical records of Tamiang Layang Regional Hospital in 2023 with a sample of 73 medical records. The results of the study obtained 57.53% of males and 42.46% of females with the highest incidence of 5-14 years old (28.77%), patients who have not attended school 39 patients (33.42%) and 52 patients (71.23%) have not worked and the highest diagnosis of pneumonia as many as 55 patients (75.34%). The antibiotic profile used by patients was ampicillin 26 prescriptions (35.61%), levofloxacin 19 prescriptions (26.02%), ceftriaxone 19 prescriptions (26.02%) and azithromycin 9 prescriptions (12.33%). The total DDD value was 80.82 DDD/100 hospitalizations with the most use being levofloxacin at 40.10 DDD/100 hospitalizations. Antibiotics included in DU90% were levofloxacin, ampicillin and azithromycin. The quality of antibiotic use using the Gyssens method was 54.80% rational prescriptions and 45.20% irrational. The chi-square value obtained LOS value had a relationship with the rationality of antibiotic use (ρ = 0.030).